PEMBERDAYAAN JAMINAN SOSIAL KETENAGAKERJAAN (BPJS) PADA PERUSAHAAN YANG DIKELOLA OLEH PIHAK SWASTA - Ni Made Ayu Fridayanti; Ni Luh Putu Erma Mertaningrum; I Nengah Merta (Jurnal Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to investigate how social security program for workers (BPJS Ketenagakerjaan) is conducted by The Kayon Resort, which is located in Tegalalang, Gianyar Regency. This research used qualitative descriptive method whose variables were the four programs of BPJS ketenagakerjaan – Work Accident Security, Old Day Security, Life Insurance, and Pension. The Data were collected through interviews and documentation. The results of the research show that the BPJS Ketenagakerjaan has not been implemented properly particularly the work accident security. This program has not been served to all workers. The old day security, life insurance and pension programs have not been realized yet because there have not been any workers who meet the criteria to receive the compensation.